Feasibility of preservation of chorda tympani nerve during noninflammatory ear surgery: A systematic review. (31st October 2017) - Ziylan, Fuat; Smeeing, Diederik P.J.; Bezdjian, A.; Stegeman, Inge; Thomeer, Hans G.X.M.
Abstract : Objective: The objective of our systematic review is to investigate the postoperative gustatory function of the chorda tympani nerve following noninflammatory ear surgery for which the chorda tympani is at risk for iatrogenic injury (stretching, handling, or sacrificing). Data Sources: PubMed and EMBASE. Review Methods: A PubMed and EMBASE databases search was conducted on November 15, 2016. Study inclusion criteria included: 1) ear surgery performed for noninflammatory ear diseases, and 2) gustatory function of the chorda tympani reported as an outcome. The quality of eligible studies was assessed using the risk of bias assessment tool for nonrandomized studies. Study characteristics and outcome data of the included studies were extracted. Results: In total 1, 094 articles were retrieved. Fourteen studies encompassing 1, 062 operated ears were included after quality assessment. Stapedectomy was the most frequent surgical procedure performed in 398 ears. The follow‐up time varied between 6 weeks and 99 months. Patients with a preserved chorda tympani were less symptomatic (24% was symptomatic) compared to patients with a stretched (53% was symptomatic) or sacrificed chorda tympani (47% was symptomatic). The recovery rate varied from 61% to 79%. The results of the electrogustometry and strip test showed a discrepancy with the subjective complaints of the patients. Conclusion: Patients with a stretched chorda tympani were slightly more symptomatic compared to patients with a sacrificed chorda tympani. Therefore, in cases for which the chorda tympani greatly hinders a proper view of the surgical field, sacrificing the nerve could be considered to maximize surgical performance and have a satisfactory postoperative result. Laryngoscope, 1904–1913, 2018